Consumer Purchase Drivers in Everwhite Skincare: Evidence from Multiple Regression Analysis - Raihan Nabila; Amin Mansur (SAN Scientific, 2026)
The purpose of this study was to determine the effects of Online Customer Reviews, Price Perception, Brand Awareness, and Consumer Income on Purchasing Decisions for Everwhite Skincare in Jakarta. The sampling technique used was purposive. Data were collected using a survey instrument. The data analysis method used was multiple regression analysis, t-test (partial) and F-test (simultaneous). The results of the study showed that: (1) Online customer reviews do not have a significant effect on purchasing decisions. (2) Price perception has a positive and significant effect on purchasing decisions. (3) Brand awareness does not affect purchasing decisions. (4) Consumer income has a significant effect on purchasing decisions. (5) Simultaneously, all independent variables have a significant effect on purchasing decisions. The managerial implications of this study indicate that business actors should pay close attention to Online Customer Reviews as the primary factor influencing consumer purchasing decisions. Positive reviews can increase customer trust in products, so companies must manage customer testimonials well. In addition, the perception of fair and competitive prices needs to be communicated clearly so that consumers feel they are getting value for money.